2020
DOI: 10.1016/j.molcel.2020.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Cdk1 Controls Global Epigenetic Landscape in Embryonic Stem Cells

Abstract: Highlights d Mice expressing analog-sensitive Cdk1 allow identification of Cdk1 substrates d Many Cdk1 substrates in ESCs are chromatin-bound at poised or transcribed genes d Cdk1 phosphorylates a large number of epigenetic regulators d Cdk1 phosphorylates and inactivates H3K79 methyltransferase Dot1l

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
104
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(108 citation statements)
references
References 97 publications
4
104
0
Order By: Relevance
“…A total of 2.5 μM CDK1i blocked the induction of CCNB1 but not CDC25B or CCNA2 in A549 cells ( Figure 7E ) and significantly reduced the induction of CCNB1 and CCNA2 but not CDC25B in the more sensitive H460 cells ( Figure S5H ). The differential effect of CDK1i on these MMB-FOXM1 target genes could reflect the differing number of CHR motifs in the gene promoters ( Fischer et al, 2016 ) or the recently identified regulation of epigenetic factors by CDK1 ( Michowski et al, 2020 ). The consistent result is that CDK1 activity remaining after 2.5 μM CDK1i was sufficient to block CHK1i-induced MMB-FOXM1 activity and increased expression of CCNB1, the mitotic activator of CDK1, during S phase.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 2.5 μM CDK1i blocked the induction of CCNB1 but not CDC25B or CCNA2 in A549 cells ( Figure 7E ) and significantly reduced the induction of CCNB1 and CCNA2 but not CDC25B in the more sensitive H460 cells ( Figure S5H ). The differential effect of CDK1i on these MMB-FOXM1 target genes could reflect the differing number of CHR motifs in the gene promoters ( Fischer et al, 2016 ) or the recently identified regulation of epigenetic factors by CDK1 ( Michowski et al, 2020 ). The consistent result is that CDK1 activity remaining after 2.5 μM CDK1i was sufficient to block CHK1i-induced MMB-FOXM1 activity and increased expression of CCNB1, the mitotic activator of CDK1, during S phase.…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, our data show that H3K79me2 increases globally during neuronal differentiation in vitro. Michowski et al 46 have recently shown that DOT1L localization and activity is controlled by CDK1 in mESC, causing global epigenetic effects during differentiation. The proposed mechanism is consistent with the global H3K79me2 increase that we observe during neuronal differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, CDK1, a candidate gene in our list, phosphorylates several proteins, including MLL2, LSD1, G9a, SUV39H2, SETD2, DOT1L, p300, KDM2A, and HDAC6, involved in histone modifications and transcription regulation. Besides, DNA maintenance methyltransferase (DNMT1) and the proteins that reverse DNA methylation, i.e., Tet1 and Tet2, are also phosphorylated by CDK1 ( Michowski et al, 2020 ). Additionally, the identification of cell cycle regulators in our screen ( Figure 1B and Supplementary Table 1 ) supports the notion that PcG/trxG system is regulated in a cell cycle dependent manner ( Laprell et al, 2017 ; Asenjo et al, 2020 ), which may play a role in faithful inheritance of epigenetic states across cell divisions.…”
Section: Discussionmentioning
confidence: 99%